Stereotactic Treatment of the Trapped Temporal Horn. (16th November 2020) - Freeman, David; Chen, Clark C.C; Warnke, Peter C
Abstract: INTRODUCTION: Current treatment of a trapped temporal horn consists primarily of ventriculo-peritoneal (VP) shunting. As a less invasive alternative, we examined an endoscopic-stereotactic approach to connect the trapped temporal horn with the prepontine cistern. METHODS: Six patients with different etiology of entrapment were studied. Using frame-based stereotaxy, image fusion and endoscopy a Rickham catheter was placed to connect both compartments. After a median follow-up of 22.1 + 7.8 months all patients improved symptomatically and the size of the temporal horn was normalized. No morbidity was encountered. RESULTS: Patient characteristics shows the typical sequence of the stereotactic planning and the catheter trajectory in relation to the pertinent anatomical structures. All patients had tumors blocking CSF flow and were symptomatic from their entrapped temporal horn with all of them having pulsating headaches and two patients showing short term memory deficits and one an expressive dysphasia. All patients improved symptomatically. All patients plagued with headache experienced resolution of the headache post-procedure. The memory deficits in two patients also improved post-procedure. Most impressively the dysphasia in one patient completely resolved within ten days of procedure. Concomitantly postop CT/MRI scans showed an immediate reduction of the size of the previously entrapped temporal horn. CONCLUSION: Endoscopic-stereotactic internal shunting of trapped temporal horns into the prepontine cistern can be done safely and it offers an elegant alternative to traditional VP shunting, by avoiding the inherent complications with this procedure.